Switching from tenofovir disoproxil fumarate to tenofovir alafenamide coformulated with rilpivirine and emtricitabine in virally suppressed adults with HIV-1 infection: a randomised, double-blind, multicentre, phase 3b, non-inferiority study. Issue 5 (May 2017) - Orkin, Chloe; DeJesus, Edwin; Ramgopal, Moti; Crofoot, Gordon; Ruane, Peter; LaMarca, Anthony; Mills, Anthony; Vandercam, Bernard; de Wet, Joseph; Rockstroh, Jürgen; Lazzarin, Adriano; Rijnders, Bart; et al.
Summary: Background: Tenofovir alafenamide, a tenofovir prodrug, results in 90% lower tenofovir plasma concentrations than does tenofovir disproxil fumarate, thereby minimising bone and renal risks. We investigated the efficacy, safety, and tolerability of switching to a single-tablet regimen containing rilpivirine, emtricitabine, and tenofovir alafenamide compared with remaining on rilpivirine, emtricitabine, and tenofovir disoproxil fumarate. Methods: In this randomised, double-blind, multicentre, placebo-controlled, non-inferiority trial, HIV-1-infected adults were screened and enrolled at 119 hospitals in 11 countries in North America and Europe. Participants were virally suppressed (HIV-1 RNA <50 copies per mL) on rilpivirine, emtricitabine, and tenofovir disoproxil fumarate for at least 6 months before enrolment and had creatinine clearance of at least 50 mL/min. Participants were randomly assigned (1:1) to receive a single-tablet regimen of either rilpivirine (25 mg), emtricitabine (200 mg), and tenofovir alafenamide (25 mg) or to remain on a single-tablet regimen of rilpivirine (25 mg), emtricitabine (200 mg), and tenofovir disoproxil fumarate (300 mg), with matching placebo, once daily for 96 weeks. Investigators, participants, study staff, and those assessing outcomes were masked to treatment group. All participants who received one dose of study drug and were on the tenofovir disoproxil fumarate regimen before screening were included in primary efficacy analyses. The primary endpoint was the proportion of participants with less than 50 copies per mL of plasma HIV-1 RNA at week 48 (by the US Food and Drug Administration snapshot algorithm), with a prespecified non-inferiority margin of 8%. This study was registered withClinicalTrials.gov, numberNCT01815736 . Findings: Between Jan 26, 2015, and Aug 25, 2015, 630 participants were randomised (316 to the tenofovir alafenamide group and 314 to the tenofovir disoproxil fumarate group). At week 48, 296 (94%) of 316 participants on tenofovir alafenamide and 294 (94%) of 313 on tenofovir disoproxil fumarate had maintained less than 50 copies per mL HIV-1 RNA (difference −0·3%, 95·001% CI −4·2 to 3·7), showing non-inferiority of tenofovir alafenamide to tenofovir disoproxil fumarate. Numbers of adverse events were similar between groups. 20 (6%) of 316 participants had study-drug related adverse events in the tenofovir alafenamide group compared with 37 (12%) of 314 in the tenofovir disoproxil fumarate group; none of these were serious. Interpretation: Switching to rilpivirine, emtricitabine, and tenofovir alafenamide was non-inferior to continuing rilpivirine, emtricitabine, tenofovir disoproxil fumarate in maintaining viral suppression and was well tolerated at 48 weeks. These findings support guidelines recommending tenofovir alafenamide-based regimens, including coformulation with rilpivirine and emtricitabine, as initial and ongoing treatment for HIV-1 infection. Funding: Gilead Sciences.